Functions and reasons for code-switching on facebook by UTAR English-Mandarin Chinese bilingual undergraduates - Choy, Wai Fong (2011)
As Facebook, one of the social-networking websites, has swiftly become one of the favoured modes of communication on the Internet, language has also been influenced in terms of its usage and practices. Code-switching, the alternate use of more than one language in a discourse, is one of the language phenomena where such changes can be traced. This research investigated on the occurrences of code-switching in asynchronous computer-mediated communication (CMC) between bilingual university students via social networking website by taking a functional approach in examining the various functions and reasons for codeswitching. The data consisted of messages posted by Faculty of Arts and Social Science (FAS) Mandarin Chinese-English bilingual students of Universiti Tunku Abdul Rahman (UTAR) on their Facebook profile pages. Data was then analysed based on an integration of Appel and Muysken’s (2006) six functions of code-switching and Malik’s (1994) ten reasons for code-switching. Findings suggested that code-switching would occur in online communication mainly to serve referential, expressive and metalinguistic functions. For more substantial results in the future, researchers may consider larger numbers of participants to observe the occurrence of code-switching in asynchronous computer-mediated communication (CMC).